ChALLENGES OF USING LANGUAGE LEARNING GAMES IN TEACHING ENGLISH FOR YOUNG LEARNERS (Konferensiyalar | Conferences, 2024)
Numerous studies have underscored the advantages of integrating games into language teaching. Lee and Luchsinger (2016) found that games can enhance student engagement and motivation, leading to improved language learning outcomes. Games also offer a fun and interactive way for students to practice language skills, reinforcing vocabulary and grammar concepts (Mehran, 2018).